Electrospinning Material Technology of the Future - Tański, Tomasz; Jarka, Paweł (IntechOpen, 2022)
This book is a summary of the latest knowledge in the field of electrospinning technology, including a detailed description of the method as well as the influence of its parameters on the structure and properties of manufactured materials. Currently, electrospinning is one of the most promising methods for the reproducible production of one-dimensional nanostructures such as nanowires, nanofibers, and fibrous mats, with high purity and dimensional accuracy. Chapters address such topics as electrospun fibrous mats in the development of active food packaging, production of structured nanofibers from natural sources, and biomass waste as an alternative source of polymeric materials in electrospinning technology, and more.